Ramanujan's convolution sum twisted by Dirichlet characters - Aygin, Zafer Selcuk (2021)
We find formulas for convolutions of sum of divisor functions twisted by the Dirichlet character (−4/∗), which are analogous to Ramanujan's formula for convolution of usual sum of divisor functions. We use the theory of modular forms to prove our results.